Tobias Putrih : 99 07 - Collins, Thom; Krimko, Stuart; Exhibition New York. Neuberger Museum of Art (Ljubljana : Gurgur editions [etc.], 2007)
"This publication was conceived as an archive of materials, both visual and textual, that illuminate the thought and art making of Tobias Putrih. At its heart are illustrations of major projects with extensive artist commentary."--p. 7.
Published in conjunction with the exhibition "Tobias Putrih: Quasi-Random"
boek
Keywords: Putrih, Tobias